2021
DOI: 10.1201/9781003193913
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Hydrodynamics and Sediment Transport in the Mekong Delta

Abstract: This research was conducted under the auspices of the Graduate School for Socio-Economic and Natural Sciences of the Environment (SENSE)CRC Press/Balkema is an imprint of the Taylor & Francis Group, an informa business

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 148 publications
(411 reference statements)
0
3
0
Order By: Relevance
“…According to Thomson & Harris [38], Tse should be taken to be the typical period of the measured wave height. The extreme high wave conditions were taken from the study of Hung et al [39] with Hse = 3 m and Tse = 7 s, respectively. Substituting Hse and Tse to Equation Table 2 contains the initial values employed for computing the shoreline position in 1991.…”
Section: Application Of Analytical Solutions For Shoreline Changementioning
confidence: 99%
“…According to Thomson & Harris [38], Tse should be taken to be the typical period of the measured wave height. The extreme high wave conditions were taken from the study of Hung et al [39] with Hse = 3 m and Tse = 7 s, respectively. Substituting Hse and Tse to Equation Table 2 contains the initial values employed for computing the shoreline position in 1991.…”
Section: Application Of Analytical Solutions For Shoreline Changementioning
confidence: 99%
“…Modeling results also showed that the sediment volume and spatial distribution changed through the simulated period according to monsoonal variation. Thanh et al (2021) focused on modeling the entire system with a process-based approach with Delft3D and Delft3D Flexible Mesh (DFM). The first model was used to detect the sediment dynamics in coastal areas, and the second model was used to allow easy coupling between 1D and 2D grids for analyzing complex river networks.…”
Section: Introductionmentioning
confidence: 99%
“…Generally few studies have been conducted on Jute mallow using protein as markers. However, this technique has been used effectively to study genetic diversity among and between genotypes in different plant species (Thanh and Hirata, 2002;Nethra et al, 2007;Chandra, 2008;Meena and Shukla, 2013). More reliable and useful information in detailing the diversity among Jute mallow genotypes can be generated by using protein markers.…”
Section: Genetic Diversity Based On Biochemical Markers I Proteinmentioning
confidence: 99%